Development of integrated support software for clinical nutrition - Pedro Siquier Homar; Manel Pinteño Blanco; Miguel Ángel Calleja Hernández; Francisco Fernández Cortés; Jesús Martínez Sotelo (Elsevier, 2015)
Objectives: to develop an integrated computer software application for specialized nutritional support, integrated in the electronic clinical record, which detects automatically and early those undernourished patients or at risk of developing undernourishment, determining points of opportunity for improvement and evaluation of the results. Methods: the quality standards published by the Nutrition Work Group of the Spanish Society of Hospital Pharmacy (SEFH) and the recommendations by the Pharmacy Group of the Spanish Society of Parenteral and Enteral Nutrition (SENPE) have been taken into account. According to these quality standards, the nutritional support has to include the following healthcare stages or sub-processes: nutritional screening, nutritional assessment, plan for nutritional care, prescription, preparation and administration. Results: this software allows to conduct, in an automated way, a specific nutritional assessment for those patients with nutritional risk, implementing, if necessary, a nutritional treatment plan, conducting follow-up and traceability of outcomes derived from the implementation of improvement actions, and quantifying to what extent our practice is close to the established standard. Conclusions: this software allows to standardize the specialized nutritional support from a multidisciplinary point of view, introducing the concept of quality control per processes, and including patient as the main customer